2020
DOI: 10.1186/s43045-020-00032-1
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and sleep disturbances among internship nursing students

Abstract: Background: Nurses are one of the most vulnerable professional groups to occupational stress and sleep problem. A relation between occupational stress and sleep problem is suggested and needs to be investigated. The aim of this descriptive study is designed to assess work stress and sleep disturbances among internship nursing students and the relation between them. Results: A total of 95 nursing internship students were subjected to Pittsburgh Sleep Quality Index (PSQI) and Expanded Nursing Stress Scale (ENSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(11 reference statements)
0
7
0
1
Order By: Relevance
“…In support of this notion, numerous cross-sectional and ambulatory studies found social stressors to harm sleep quality [15,21,[23][24][25][26]. Additionally, other occupational stressors, such as the number of patient interactions and working hours, have been found to impair sleep indicators [27][28][29]. For Sonnentag [17], the fact that sleep is impaired when job stressors are high is paradoxical, as the experience of exactly such high stressors would call for effective recovery processes to set in (i.e., good sleep); she terms this phenomenon 'the recovery paradox'.…”
Section: Physiological Sleep Quality As An Indicator For Health Impai...mentioning
confidence: 92%
“…In support of this notion, numerous cross-sectional and ambulatory studies found social stressors to harm sleep quality [15,21,[23][24][25][26]. Additionally, other occupational stressors, such as the number of patient interactions and working hours, have been found to impair sleep indicators [27][28][29]. For Sonnentag [17], the fact that sleep is impaired when job stressors are high is paradoxical, as the experience of exactly such high stressors would call for effective recovery processes to set in (i.e., good sleep); she terms this phenomenon 'the recovery paradox'.…”
Section: Physiological Sleep Quality As An Indicator For Health Impai...mentioning
confidence: 92%
“…Tyrimai rodo, kad slaugos studentai profesinių praktikų metu patiria nuo vidutinio iki didelio stiprumo stresą. Stresas siejamas su procedūrų atlikimu, technologijų ir įrangos naudojimu, konfliktiniais santykiais su personalu, pacientais ir jų artimaisiais [2][3][4][5][6][7]. Tyrimai rodo, kad netgi praktinio mokymo vieta turi įtakos slaugos studentų streso raiškai.…”
Section: įVadasunclassified
“…Although many studies have been conducted on the relationship between job stress and sleep quality or the sleep disturbance of nurses and nursing students [ 21 , 22 ], there are few studies reporting the relationship between these two factors with turnover intention. However, some studies reported the relationship between turnover intention and each job stress or sleep problem.…”
Section: Introductionmentioning
confidence: 99%